Precautionary complications on hypertension with Health Belief Model (HBM) approach: A descriptive study of health center community in The Garut Region of Indonesia - Nurhandiya, Vina; Yani, Desy Indra; Shalahuddin, Iwan (Universitas Aisyah Pringsewu, 2020)
Hypertension is not a contagious disease that becomes health problems with high prevalence. Hypertension is at risk for complications. The application theory of the health belief model (HBM) is an effort to prevent hypertension by identifying the patient's perception. The purpose of this study was to determine the description of the prevention of complications in hypertensive patients at the Tarogong Garut Health Center using the health belief model (HBM) approach. The research method used descriptive quantitative. The population of hypertension patients at Tarogong Public Health Center by 72 samples of patients. Data analysis used a percentage value of each domain presented in the form of a frequency distribution table to each variable studied. The results showed that from 5 dominant areas both were perception of barrier good (4.2 percent) and deficient (95.8 percent), deficient of susceptibility perception (100 percent), lacking severity perception (100 percent), lacking benefits perception (100 percent), and deficient of cues to action (100 percent). The conclusion of this study if somebody has a good perception of their illness, then they will focus on the prevention and control the condition of health problems. If the perception is not good, then somebody will tend to ignore health problems. Nurses should be able to provide knowledge about hypertension and the complications caused by the disease and can raise the awareness of patients to perform regular blood pressure checks. Karakteristik pasien stroke: Deskripsi analitis pada pasien rawat jalan di rumah sakit di Semarang IndonesiaAbstrak: Hipertensi penyakit tidak menular yang menjadi masalah kesehatan dengan prevalensi yang tinggi. Hipertensi beresiko terhadap komplikasi. Penerapan teori health belief model (HBM) digunakan sebagai upaya pencegahan hipertensi dengan mengidentifikasi persepsi pasien. Tujuan penelitian ini adalah mengetahui gambaran pencegahan komplikasi pada pasien hipertensi di Puskesmas Tarogong Garut menggunakan pendekatan health belief model (HBM). Metode penelitian menggunakan deskriptif kuantitatif. Populasi pasien hipertensi di Puskesmas Tarogong dengan jumlah sampel 72 pasien. Analisa data menggunakan persentase nilai dari setiap domain, yang disajikan dalam bentuk tabel distribusi frekuensi terhadap masing-masing variabel yang diteliti. Hasil penelitian menunjukan bahwa dari 5 domain yang dominan baik adalah persepsi hambatan baik (4,2 persen) dan kurang baik (95,8 persen), persepsi kerentanan kurang baik (100 persen), persepsi keparahan kurang baik (100%), persepsi manfaat kurang baik (100 persen), dan isyarat bertindak kurang baik (100 persen). Kesimpulan pada penelitian ini jika persepsi seseorang baik terhadap penyakitnya maka seseorang akan terfokus pada pencegahan dan mengontrol kondisi gangguan kesehatannya, dan jika persepsinya kurang baik maka seseorang akan cenderung mengabaikan masalah kesehatannya. Perawat harus bisa memberikan pengetahuan mengenai penyakit hipertensi dan komplikasi yang ditimbulkan dari penyakitnya, serta bisa menumbuhkan kesadaran pasien untuk melakukan pemeriksaan tekanan darah secara rutin.